A holistic approach in epidemics - Tsagkarliotis, Ioannis; Rachaniotis, Nikolaos P. (Frontiers in Public Health, 2023)
This paper explores the concept of a holistic approach in preventing and responding to epidemics. Epidemics are defined as the occurrence of an illness or health-related event exceeding normal expectations within a specific community or region. Holism emphasizes viewing systems as a whole rather than a collection of parts. In the context of epidemics, a holistic approach considers not only medical interventions but also social, economic, psychological and environmental factors that influence disease transmission and management. The impact of climate change on epidemic response, the understanding of the significance of animal health and agriculture, the consideration of art, culture and societal factors, the exploration of the use of technology and innovation, the addressing of limitations in resources and the provision of enhanced support for the mental and emotional well-being of individuals and affected communities, are parts of this holistic approach. By integrating them, innovative practices as well as cross-sectoral and interdisciplinary techniques can be employed. Such an approach has the potential to enhance epidemic prevention and response strategies, ultimately contributing to positive public health outcomes.